Ride the devil's herd : Wyatt Earp's epic battle against the West's biggest outlaw gang - Boessenecker, John, 1953- (Hanover Square Press, 2020)
"Wyatt Earp is regarded as the most famous lawman of the Old West, best known for his role in the Gunfight at the O.K. Corral in Tombstone, Arizona. But the story of his two-year war with a band of outlaws known as the Cowboys has never been told in full. The Cowboys were the largest outlaw gang in the history of the American West. After battles with the law in Texas and New Mexico, they shifted their operations to Arizona. There, led by Curly Bill Brocius, they ruled the border, robbing, rustling, smuggling and killing with impunity until they made the fatal mistake of tangling with the Earp brothers. Drawing on groundbreaking research into territorial and federal government records, John Boessenecker's Ride the Devil's Herd reveals a time and place in which homicide rates were fifty times higher than those today. The story still bears surprising relevance for contemporary America, involving hot-button issues such as gang violence, border security, unlawful immigration, the dangers of political propagandists parading as journalists, and the prosecution of police officers for carrying out their official duties. Wyatt Earp saw it all in Tombstone." --Amazon.